2000
DOI: 10.1046/j.1365-2117.2000.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Synsedimentary tensional features in Upper Triassic shallow‐water platform carbonates of the Carnian Prealps (northern Italy) and their importance as palaeostress indicators

Abstract: The extensive shallow‐water carbonate platform deposits of the Dolomia Principale Formation (Southern Alps, northern Italy) accumulated during the Late Triassic, a time of plate‐scale reorganization and rifting. Synsedimentary tensional features such as fractures, neptunian dykes, normal faults, shatter breccias and laterally discordant intraformational breccias have been studied within a well‐preserved platform‐to‐basin transition in the Monte Pramaggiore area (Carnian Prealps). These tensional features follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 29 publications
1
42
0
4
Order By: Relevance
“…This kind of geometry points to the aggradation of the system in the Middle Norian. Similar aggradation of the same age was reported also from the Carnian Prealps (Italy) connected with the Middle-Late Norian extensional tectonic activity, related to the aborted westward opening of the Neotethys Ocean and the incipient rifting phase of the Ligurian-Piedmont Ocean (Carulli et al, 1998;COZZi, 2000;COZZi, 2002;COZZi & Hardie, 2003). The Alaunian aggradation is also reported from the Northern Calcareous Alps (berra, 1995;KryStyn et al, 2009).…”
Section: Discussionsupporting
confidence: 54%
“…This kind of geometry points to the aggradation of the system in the Middle Norian. Similar aggradation of the same age was reported also from the Carnian Prealps (Italy) connected with the Middle-Late Norian extensional tectonic activity, related to the aborted westward opening of the Neotethys Ocean and the incipient rifting phase of the Ligurian-Piedmont Ocean (Carulli et al, 1998;COZZi, 2000;COZZi, 2002;COZZi & Hardie, 2003). The Alaunian aggradation is also reported from the Northern Calcareous Alps (berra, 1995;KryStyn et al, 2009).…”
Section: Discussionsupporting
confidence: 54%
“…2), south of the Bükk Mts in North Hungary (Cserepes et al 2008 (Grad and Ogorelec 1980;Ramovš 1989;Gianolla et al 1998;Cozzi 2000;Dozet 2000), very similar to what was encountered in the wells south of the BAL.…”
Section: Mid-transdanubian Composite Unitmentioning
confidence: 63%
“…The sedimentary infill of open fractures and cavities in seabed, referred to as neptunian dykes, consists of sediment derived from the sidewalls and from above (Winterer and Sarti, 1994;Cozzi, 2000;Črne et al, 2007). The origin of neptunian dykes is widely attributed to seismic activity (Playford, 1980;Winterer and Bosellini, 1981;Lehner, 1991;Montenat et al, 1991;Cozzi, 2000), although similar features have also been reported from the surfaces of submarine slides (Winterer et al, 1991;Winterer and Sarti, 1994).…”
Section: Deformation Features 421 Neptunian Dykesmentioning
confidence: 90%
“…The dyke parabreccia component was formed by a brittle disintegration of the fissure sidewalls. The sandstone fragments show no evidence of weathering or dissolution, and their sharp edges suggest that the sand was wellcompacted and perhaps slightly cemented prior to its rupture (see Cozzi, 2000).…”
Section: Deformation Features 421 Neptunian Dykesmentioning
confidence: 99%